Structure-driven dielectric reinforcement in NiO via rare earth Y2O3 integration: A correlated lattice-interface evolution study - Gurgenc, Ezgi; Macit, Cevher Kursat; Güner, Melek; Gurgenc, Turan; Özkan, Betül Çiçek; Aksakal, Bünyamin (Elsevier Sci Ltd, 2026)
This study investigates the structure-property relationships governing the dielectric and electrical behavior of NiO nanoparticles reinforced with yttrium oxide (Y2O3) in the range of 1-10 wt%. Nanocrystalline NiO and NiO-Y2O3 composites were synthesized via a controlled nonaqueous sol-gel route to ensure compositional homogeneity and microstructural reproducibility. Comprehensive characterization was performed using XRD, Williamson-Hall and Rietveld analyses, XPS, FT-IR and Raman spectroscopy and FE-SEM/EDX to elucidate lattice evolution, defect chemistry, interfacial architecture and microstructural changes induced by Y2O3 incorporation. XRD analysis confirmed that the cubic NiO structure is preserved across all compositions, while shifts of diffraction peaks toward higher 2 theta angles revealed lattice contraction. The lattice parameter decreased from 4.194 & Aring; for pure NiO to 4.164 & Aring; for the 10 wt% Y2O3 composition, accompanied by compressive microstrain quantified by Williamson-Hall and validated by full-pattern refinement. XPS demonstrated substitutional Y3+ incorporation and an increased population of defect-related oxygen species, indicating vacancy-mediated charge compensation. Raman and FT-IR analyses revealed phonon softening, band broadening, and enhanced defect-activated vibrational features, consistent with strain- and interface-induced lattice disorder. Dielectric measurements conducted in the 1 kHz-1 MHz frequency range showed improved dielectric performance with increasing Y2O3 content. At 1 kHz, the dielectric constant increased from 6.61 for pure NiO to 9.33 at 10 wt% Y2O3, corresponding to an enhancement of similar to 41%, while AC conductivity increased by similar to 26% (from 1.60 & times; 10(-8) to 2.03 & times; 10(-8) S/cm). Cole-Cole analysis confirmed non-Debye relaxation dominated by Maxwell-Wagner interfacial polarization and defect-assisted charge transport, yielding composition-tunable dielectric dispersion and conduction. Overall, Y2O3 acts as an effective defect and interface engineering agent in NiO, enabling controlled lattice compression, enhanced interfacial polarization, and tunable dielectric response. These findings highlight the potential of NiO- Y2O3 nanocomposites for high-k dielectric layers, capacitive energy storage, varistor-type components and fast-response sensor platforms.
Keywords: Rare earth element oxide; Semiconductor; Dielectric properties; Nanocomposite; Energy material